Duplicity in Novel by M. Spark “Aiding and Abetting” - E. V. Ushakova (Научный диалог, 2021)
The article reveals the specifics of the functioning of the phenomenon of duplicity  in  the novel by the English writer M. Spark “Aiding and Abetting” (2000). The scientific novelty lies in the fact that this work is viewed from this angle for the first time. An overview of a number of existing approaches to the phenomenon of duality in modern literary criticism is presented. The author analyzes pairs of the main characters of the novel, who are doubles, revealed in similar situations related to the themes of fraud and crime. It is shown that in the novel “Aiding and Abetting” the characters play the roles of both antagonists and carnival counterparts. Particular attention is paid to the  combination  inherent in M. Spark’s work in the works of satirical orientation and postmodern play, which is reflected in the change of the narrative perspective, ambiguity and uncertainty of the finale. The meaning of the title of the work is revealed in the context of the realization of the motive of duality, the main moral problems posed in the novel are revealed. The author comes to the conclusion that through the use of doubles, Spark describes the vices of society and the moral degradation of a person.